2010
DOI: 10.1007/s12645-010-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and nanotechnology approaches for capturing circulating tumor cells

Abstract: Circulating tumor cells (CTC) are cells that have detached from primary tumors and circulate in the bloodstream where they are carried to other organs, leading to seeding of new tumors and metastases. CTC have been known to exist in the bloodstream for more than a century. With recent progress in the area of micro- and nanotechnology, it has been possible to adopt new approaches in CTC research. Microscale and nanoscale studies can throw some light on the time course of CTC appearance in blood and CTC overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Clinically, labor-intensive and time-consuming laboratory separation techniques, including centrifugation, filtration and magnetic enrichment, followed by immunological assays and microscopic analyses of the captured CTCs, are relied upon to provide information for cancer staging [35]. Detection of CTCs is challenging due to the low number of CTCs present in the background of normal blood cells, and the quantity of CTCs is likely to change with time, reflecting the discontinuous process of cell migration from a tumor into the vasculature.…”
Section: Clinical Detection Of Cancer Invasion and Early-stage Metastasismentioning
confidence: 99%
“…Clinically, labor-intensive and time-consuming laboratory separation techniques, including centrifugation, filtration and magnetic enrichment, followed by immunological assays and microscopic analyses of the captured CTCs, are relied upon to provide information for cancer staging [35]. Detection of CTCs is challenging due to the low number of CTCs present in the background of normal blood cells, and the quantity of CTCs is likely to change with time, reflecting the discontinuous process of cell migration from a tumor into the vasculature.…”
Section: Clinical Detection Of Cancer Invasion and Early-stage Metastasismentioning
confidence: 99%
“…A further motivation for continuous monitoring of the circulation is evident considering the prevalence of CTC: reports have identified as few as 1 CTC per 7.5 mL patient sample 4. On the basis of this estimate, there is a low probability of capturing any CTC in a single blood sample of a few milliliters 14. A device that would allow for screening of the entire circulation would minimize the chance of CTC evading the device.…”
Section: In Vivo Ctc Manipulation Techniquesmentioning
confidence: 99%
“…Studies have found that unique adhesive properties of the luminal surface of particular organ vasculature are sufficient to explain the habitual homing of certain cancers to specific secondary tissues 6,10–13. Thus, it is evident that the presence of CTC in the circulatory system is a necessary phenomenon in cancer progression, and researchers and physicians have recently begun to recognize the relevance and use of CTC for diagnosis and treatment 14…”
Section: Introductionmentioning
confidence: 99%
“…For example, micro-and nano-actuation technologies are being applied in targeted drug delivery systems [19][20][21] , employed as implantable devices to augment failing organs 22 , and used for capture of circulating tumor cells towards early metastatic cancer detection 23 .…”
Section: VImentioning
confidence: 99%